2002
DOI: 10.1074/jbc.m205862200
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of α-Helicity in the HIV-1 Inhibitory Peptide DP178 Leads to an Increased Affinity for Human Monoclonal Antibody 2F5 but Does Not Elicit Neutralizing Responses in Vitro

Abstract: The synthetic peptide DP178, derived from the carboxyl-terminal heptad repeat region of human immunodeficiency virus type 1 GP41 protein is a potent inhibitor of viral-mediated fusion and contains the sequence ELDKWA, which constitutes the recognition epitope for the broadly neutralizing human monoclonal antibody 2F5. Efforts at eliciting a 2F5-like immune response by immunization with peptides or fusion proteins containing this sequence have not met with success, possibly because of incorrect structural prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
118
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 114 publications
(122 citation statements)
references
References 57 publications
3
118
1
Order By: Relevance
“…2 A) but not by the fluorescein-specific scFv COLIN (data not shown), thus confirming the specificity. The D5 scFv also blocked HIV infection in a single-cycle infectivity assay (20) (Fig. 2B), indicating that D5 can inhibit HIV entry in multiple assay formats.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2 A) but not by the fluorescein-specific scFv COLIN (data not shown), thus confirming the specificity. The D5 scFv also blocked HIV infection in a single-cycle infectivity assay (20) (Fig. 2B), indicating that D5 can inhibit HIV entry in multiple assay formats.…”
Section: Resultsmentioning
confidence: 99%
“…Measurement of HIV infection of p4-2͞R5 cells by using a chemiluminescent ␤-galactosidase substrate was done as described (20). BaL and HXB2 were purchased from Advanced Biotechnologies (Columbia, MD); 89.6 was grown in peripheral blood mononuclear cells, and vesicular stomatitis virus-G-pseudotyped HIV was made by transfection as described (21).…”
Section: Antiviral Assaysmentioning
confidence: 99%
“…In addition to simple linear or structurally constrained peptide immunogens, recombinant protein immunogens including displays of constrained 2F5 epitope in the contexts of various protein scaffolds have been also pursued [28][29][30][31][32][33][34][35][36][37]. While inducing high antibody titers against the primary amino acid sequence of the epitope, these immunogens have failed to elicit NAbs against primary HIV-1.…”
Section: Introductionmentioning
confidence: 99%
“…10,20,[23][24][25][26] First, synthetic peptide antigens representing monomeric gp41 peptides are conformationally unstable. Since stability and bioactive conformation are intimately associated with trimeric quaternary structure, they are difficult to duplicate using monomeric peptides.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, attempts to exploit these peptides as immunogens, alone or with additional variable regions, have been unsuccessful. [23][24][25][26] Golding et al 10 and Louis et al 20 showed that antibodies gp41 Protein Mimetics Elicit Neutralizing Antibodies 321 generated against complexed peptides or engineered trimeric peptides based on the N-HR or C-HR domains possess viral neutralizing activity. These results suggest that targeting the bioactive conformations of the N-HR or C-HR domains is a viable vaccine design strategy.…”
Section: Introductionmentioning
confidence: 99%